2018
DOI: 10.1108/qae-06-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ISO quality management systems on primary and secondary schools in Spain

Abstract: Purpose The purpose of this study is to evaluate the application of quality management systems (QMS) based on international standards of quality in education (ISO 9001:2008) and ascertain the influence of this quality model on primary and secondary schools in Spain. Design/methodology/approach The study was conducted in 26 publicly funded, private schools in Spain. The research design was a three-phase, mixed-methods evaluation. In all, 809 teachers answered the main survey questionnaire in Phase 3, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…However, increasing theoretical knowledge about this impact is currently badly needed. In this sense, it is difficult to compare the results obtained in this study with other similar ones, due to the scarce existence of scientific literature related to the application of ISO 9001 standard in the field of education and, more specifically, in non-university educational stages (as pointed out by authors such as Sweis et al, 2020;Arribas-D ıaz and Mart ınez-Mediano, 2018;Espiñeira-Bell on, Espiñeira-Bell on et al, 2016;Becerra and Corredor, 2015). This scarcity of research has been confirmed by our research group in the successive and exhaustive bibliographic reviews carried out in recent years for the numerous research studies on the application of QMS, specifically on ISO standards (Fern andez-Cruz et al, 2020;Rodr ıguez-Mantilla et al, 2020;Fern andez-Cruz et al, 2019;Fern andez-D ıaz et al, 2017;Fern andez-D ıaz et al, 2016;Rodr ıguez-Mantilla and Fern andez-D ıaz, 2013).…”
Section: Discussionmentioning
confidence: 80%
“…However, increasing theoretical knowledge about this impact is currently badly needed. In this sense, it is difficult to compare the results obtained in this study with other similar ones, due to the scarce existence of scientific literature related to the application of ISO 9001 standard in the field of education and, more specifically, in non-university educational stages (as pointed out by authors such as Sweis et al, 2020;Arribas-D ıaz and Mart ınez-Mediano, 2018;Espiñeira-Bell on, Espiñeira-Bell on et al, 2016;Becerra and Corredor, 2015). This scarcity of research has been confirmed by our research group in the successive and exhaustive bibliographic reviews carried out in recent years for the numerous research studies on the application of QMS, specifically on ISO standards (Fern andez-Cruz et al, 2020;Rodr ıguez-Mantilla et al, 2020;Fern andez-Cruz et al, 2019;Fern andez-D ıaz et al, 2017;Fern andez-D ıaz et al, 2016;Rodr ıguez-Mantilla and Fern andez-D ıaz, 2013).…”
Section: Discussionmentioning
confidence: 80%
“…Quality and TQMa broadly acknowledged philosophy of improvement to organizational performance and customer satisfaction (Deming, 1986), are common subjects of investigation in the scholarly literature. Lunenburg (2010) explains that while TQM originated in applications in manufacturing and service organizations, it can also be implemented in schools.…”
Section: Total Quality Management In Educationmentioning
confidence: 99%
“…Johnson and Golomskiis (1999) assert that leaders should establish unified goals in education and be responsible for ensuring that relevant parties are fully involved. Furthermore, continuous evaluation should be carried out through internal and external audits that enable analysis of quality indicators and non-conformance (Arribas Díaz and Martínez-Mediano, 2018). Murgatroyd and Morgan (1993) construct a TQM framework that delivers tools from the context of schooling to school-based management.…”
Section: Total Quality Management Practices and Modelsmentioning
confidence: 99%